Atomic-resolution structure imaging of defects and interfaces in compound semiconductors. Issue 4 (November 2020) - Smith, David J.
Abstract: This review focuses on the use of atomic-resolution structure imaging in the transmission electron microscope (TEM) to determine atomic arrangements at defects and interfaces in compound semiconductor (CS) thin films and heterostructures. The article begins with a brief overview of relevant sample preparation techniques and a short description of suitable TEM operating modes and some practical requirements for atomic-structure imaging. Atomically-resolved structural defects, including different types of dislocations associated with stacking faults and twin boundaries, are then described. Attention is directed towards isovalent and heterovalent heterostructures with several types of interfacial defects. Critical issues associated with assessing interface abruptness and chemical intermixing, which directly impact proposed CS device applications, are also considered. Finally, ongoing challenges and prospects for future atomic-resolution studies of CS materials are briefly discussed.